Plastid genome variation with phylogenetic implications within Anaphalis (Asteraceae: Gnaphalieae) - Huang, Ding-Wei; Meng, Ying; Wu, Jue; Liu, Zi-Han; Wen, Jun; Nie, Ze-Long (Phytotaxa, 2026)
Anaphalis is the largest genus in tribe Gnaphalieae of Asteraceae in Asia, with more than 110 species distributed mainly in tropical to temperate Asia. The interspecific relationships and evolution within Anaphalis are complex and remain controversial, with little attention for their chloroplast evolution at the genomic level. In this study, we sequenced and assembled chloroplast genomes, performing comparative and phylogenetic analyses on 32 representative species of Anaphalis. Our results revealed that these chloroplast genomes exhibit a typically circular quadripartite structure ranging in length from 152,396 to 153,573 bp with a total of 131 to 132 genes, including 87 protein-coding, 36–37 tRNA, and 8 rRNA genes. The phylogenetic analyses suggested that Anaphalis is polyphyletic and nested with Helichrysum and Pseudognaphalium, which are clustered into two groups as clades I and II. The overall genome length of clade I was relatively smaller than that of clade II, possibly due to less insertion with more deletions in intergenic regions of the former. The trnT-GGU gene is presented as pseudogene in clade II but is absent in clade I. The rpl22 gene shows significantly higher positive selection from most species of clade I than those in clade II, probably related to environmental adaptations of species from clade I survived in high-altitude mountains. The results of the comparative and phylogenetic analyses provide valuable references for further research studies of classification, phylogenetic relationships and genomic adaptation of Anaphalis species.